Complementary crops and landscape features sustain wild bee communities. Issue 4 (26th April 2018) - Martins, Kyle T.; Albert, Cécile H.; Lechowicz, Martin J.; Gonzalez, Andrew
Abstract: Wild bees, which are important for commercial pollination, depend on floral and nesting resources both at farms and in the surrounding landscape. Mass‐flowering crops are only in bloom for a few weeks and unable to support bee populations that persist throughout the year. Farm fields and orchards that flower in succession potentially can extend the availability of floral resources for pollinators. However, it is unclear whether the same bee species or genera will forage from one crop to the next, which bees specialize on particular crops, and to what degree inter‐crop visitation patterns will be mediated by landscape context. We therefore studied local‐ and landscape‐level drivers of bee diversity and species turnover in apple orchards, blueberry fields, and raspberry fields that bloom sequentially in southern Quebec, Canada. Despite the presence of high bee species turnover, orchards and small fruit fields complemented each other phenologically by supporting two bee genera essential to their pollination: mining bees ( Andrena spp.) and bumble bees ( Bombus spp.). A number of bee species specialized on apple, blueberry, or raspberry blossoms, suggesting that all three crops could be used to promote regional bee diversity. Bee diversity (rarefied richness, wild bee abundance) was highest across crops in landscapes containing hedgerows, meadows, and suburban areas that provide ancillary nesting and floral resources throughout the spring and summer. Promoting phenological complementarity in floral resources at the farmstead and landscape scales is essential to sustaining diverse wild bee populations.